Sociālas valsts princips kā vispārējais tiesību princips - Jansone, Viktorija (Latvijas Universitāte, 2011)
Dotā bakalaura darba nosaukums „Sociālas valsts princips, kā vispārējais tiesību princips”. Darbā autore izpēta sociālas valsts tiesiskās koncepcijas vēsturi un šā principa vēsturiskus, aksioloģiskus un funkcionālus aspektus. Pamatojoties uz sociālas valsts jeb sociāli atbildīgas valsts principa piemērošanas problemātikas pētījumā tiek pierādīta galvenā tēze: sociālas valsts principa nodrošināšana ir īpaši būtiska valsts ekonomiskas lejupslīdes apstākļos, nepieļaujot sociāli netaisnīgu lēmumu īstenošanu un iedzīvotāju pamattiesību nepamatotu ierobežošanu. Darbā autore atbild uz nostādītajiem jautājumiem par sociālo tiesību būtibu un darbības specifiku Latvijas tiesību sistēmā, sociālas valsts principa tiesisku iedarbību un piemērošanu Latvijas judikatūrā, sociālo tiesību ierobežojumu leģitīmajiem mērķiem. Bakalaura darba apjoms ir 64 lapaspuses, 4 pamatnodaļas un 1 pielikums. Pētījuma mērķa sasniegšanai tika izmantota literatūra latviešu, angļu, vācu un krievu valodās, pētīti Eiropas Savienības normatīvie akti, Starptautiskie līgumi, pasaules valstu konstitūcijas un likumi, Latvijas Republikas Satversme un sociālo tiesību normatīvie akti, Satversmes tiesas un Augstākās tiesas judikatūra.

The title of presented bachelor thesis is „ The social state as a general principle of law”. During the development of thesis conception the author analyzes the essence of the social state principle application in Latvian social legislation and Constitutional Court. A target of thesis was set to analyze the social state historical concept, functional aspects of the basis of the social state and prove the following proposition: ensuring the social state principle is especially relevant in the national economic downturn, avoiding socially unjust decision and implementation of population undue restriction of fundamental rights. In the first paragraph the author explore the nature of the general principles of law and the social state principle, search the role of it in the local social security law. Second paragraph is devoted to analyze the social state principle enforcement on the Latvian social rights and social security systems. Also author analyzes the social state principle application in Latvian Constitutional Court. In the third paragraph author controversy the problems of realization of social rights during the economic crisis. During the study of general thesis author concluded that thanks to the constitutional evaluation of the social state principle, there is a slight possibility that the country has achieved in a relatively conceptual unity and social rights must be protected at the highest level, regardless of the economic situation. The social protection and social welfare provision is a constitutional value and the government need to effectively redistribute the common good and to balance the income with expenses. In spite of the social security financial expenditure-intensive, the state has to maintain the level of social security, also looking for alternative budgetary consolidation. There are total of 64 pages, including 3 major paragraphs, 1 annex with 1 table. There were used 94 literature sources during the development of this thesis in Latvian, English, German and Russian languages.
The social state as a general principle of Law
Keywords: Juridiskā zinātne